DIGITALISASI PEMERATAAN BANTUAN SOSIAL DENGAN INOVASI “MY NUTERA” DI KELURAHAN TAMANSARI BANDUNG - Friska Setya; Indri Sri Rahayu; Mega Zahra Rahman; Mikhael Kristian Hadhitya Chandra Widiyanto; Zalfa Jasmina Putri (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2022)
Social Assistance or Bansos is the provision of assistance both cash and non-cash which is carried out selectively to people with certain conditions to improve welfare. The distribution of social assistance often encounters problems due to imperfect data collection, lack of socialization regarding the public's understanding of the social assistance provided, which results in inequality of social assistance. As for digitization in improving data and updating data regularly. Therefore, in this journal, a review of field observations will be carried out to see how the distribution of social assistance is in the Tamansari village. The results achieved are in the form of more detailed and accurate data management regarding the distribution of social assistance so that people can be more prosperous.